READING AND WRITING CHALLENGES IN DYSLEXIA: A REVIEW FROM A PSYCHOLINGUISTICS PERSPECTIVE - Fahria Malabar; Nurlaila Husain; Nur Qalbi Andini; Usman Pakaya (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Dyslexia is a common yet complex learning disorder that interferes with an individual’s ability to read and write fluently, despite adequate intelligence and access to education. This study employs a qualitative literature review to examine dyslexia through a psycholinguistic lens, focusing on how deficits in phonological processing, lexical access, and working memory contribute to the core challenges in reading and writing. Common manifestations—including substitution, omission, and inversion errors in reading, as well as spelling difficulties, morphological simplification, and disorganized sentence structure in writing—are discussed in relation to underlying cognitive mechanisms. The review also explores the multifactorial causes of dyslexia, emphasizing the roles of genetic, neurobiological, cognitive, and environmental factors. In addressing intervention strategies, the study highlights structured literacy approaches, the use of assistive technologies, and the importance of teacher training and policy support. By synthesizing current research, this review underscores the need for early identification and individualized educational responses. Ultimately, it contributes to a more holistic understanding of dyslexia and supports the development of inclusive practices that respond to the diverse needs of dyslexic learners.